Association of maternal depression and hypothyroidism with infant gastroschisis: a population-based cohort study in Canada - Liu, Shiliang; Claude, Hughes; Yong, Shin Jie *; Chen, Dunjin (Nature Publishing Group, 2023)
Gastroschisis has increased globally over recent decades, and this increase has not been explained by identified risk factors. We conducted a population-based study of infants born in Canada, 2004–2020. We used “winter” months (i.e., September through June) and northern areas of residence as indicators of less sunlight/less active lifestyle, while “summer” (i.e., July and August) and southern areas were considered as reference. Rate of gastroschisis for infants conceived in winter (3.4 per 10,000) was higher than for infants conceived in summer (2.2 per 10,000; p < 0.001). Exposure to winter, and northern area, hypothyroidism, substance or tobacco uses and depressive disorder were initially identified as risk factors for gastroschisis. There was a significant interaction between women < 24 years of age and 2-month conception intervals (rate ratio (RR): 1.42 (95% confidence interval [CI] 1.19–1.70). The association of maternal depression (mean ratio 2.19, 95% CI 0.87–3.50, p = 0.001) with infant gastroschisis was mediated by hypothyroidism (mean ratio 1.04, 95% CI 1.01–1.07, p < 0.001), whereas substance use, hypothyroidism, tobacco smoking and gestational diabetes showed 5.5-, 3.1-, 2.7-, and 1.2-fold associations, respectively, with maternal depression. In contrast to the summer conception interval of low gastroschisis risk, an elevated risk of gastroschisis spans the other ten months in association with higher levels of stress adaptation, thermoregulation and metabolism, reproduction, and growth effector hormones. Our findings suggest that periconception depression with mediation by hypothyroidism, may play a causal role in offspring gastroschisis.